Doing the right thing - Isabella Quadrelli; Anna Uboldi (Oñati Socio-Legal Series)
The study explores the legal consciousness of young people in the context of COVID-19 pandemic, concerning the management of personal relationships vis-à-vis the legal regulation enacted by the Italian government. We aim to account for the forms of legality that have granted to sustain, criticize, engage, and resist the law, and to understand the mechanisms that contributed to shaping specific experiences of legality. We refer to a theoretical framework based on legal consciousness, the Neo-Bourdieusian approach to moral judgment and Douglas’s theory of risks. Based on the analysis of 70 narratives, our findings show different ways of experiencing the law by young people. Different recurring narratives can be identified: individual translation, trust in procedure, fatalistic claims, and cooperative criticism. These narratives are not fixed attributes of individuals but recurring repertoires of perceptions and practices that emerge from specific interaction contexts where pre-reflective dispositions and conscious deliberation intersect.